2018
DOI: 10.1002/lary.27237
|View full text |Cite
|
Sign up to set email alerts
|

Height is an independent risk factor for postintubation laryngeal injury

Abstract: Objectives/Hypothesis Intubation is an essential component of intensive care, yet it does have potential complications. Posterior glottic stenosis (PGS) is among the most severe sequela. Risk factors are poorly understood. One hypothesis is that large endotracheal tubes (ETTs) in smaller airways may increase risk. Because tracheal diameter is proportional to height, we designed a case‐control study to evaluate the association between intensive care unit (ICU)‐patient height (proxy for tracheal diameter) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…We found that height alone was the best predictor of SL, which has not previously been reported 23 . Shorter height has been independently associated with increased odds of developing posterior glottic stenosis in intubated adults 36 . Interestingly, sex and presence of a syndrome also did not have an effect beyond that predicted by patient height alone, and the same formula for predicting SL in nonsyndromic children could be used in syndromic children.…”
Section: Discussionsupporting
confidence: 48%
“…We found that height alone was the best predictor of SL, which has not previously been reported 23 . Shorter height has been independently associated with increased odds of developing posterior glottic stenosis in intubated adults 36 . Interestingly, sex and presence of a syndrome also did not have an effect beyond that predicted by patient height alone, and the same formula for predicting SL in nonsyndromic children could be used in syndromic children.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, patient‐specific risk factors such as comorbid conditions have been associated with increased risk for subsequent laryngotracheal injury following intubation. These factors include type 2 diabetes mellitus, obesity, hypertension, cardiovascular disease, and smoking 38‐40,43,44 . It is thought that these factors may predispose patients to ETT‐induced mucosal injury of the larynx and impaired healing once injury occurs 40 .…”
Section: Discussionmentioning
confidence: 99%
“…These factors include type 2 diabetes mellitus, obesity, hypertension, cardiovascular disease, and smoking. [38][39][40]43,44 It is thought that these factors may predispose patients to ETT-induced mucosal injury of the larynx and impaired healing once injury occurs. 40 Several of these comorbidities have also been associated with increased severity of COVID-19 infection, 42,45 suggesting that not only are these patients at greater risk of intubation but also at increased risk of subsequent intubation-related laryngeal sequelae.…”
Section: Laryngeal Complaints Physical Examination Findings and Dmentioning
confidence: 99%
“…This may be secondary to ETT that are too large for shorter patients. 16 Larger multicenter studies may be important for implementing updated algorithms for ETT selection.…”
Section: Discussionmentioning
confidence: 99%